Metabolite Profiling of Java Turmeric (Curcuma xanthoriza) Essential Oil with Different Harvest Times - Dewi Anggraini Septaningsih; Rudi Heryanto; Mohamad Rafi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Java turmeric (Curcuma xanthoriza) is one of the native plants from Indonesia. Java turmeric is known as a medicinal plant with a high content of volatile oils. In this study, we investigated the chemical profile of java turmeric essential oil obtained by hydrodistillation associated with different harvesting times of the rhizome (7, 9, and 11 months). The constituent of the essential oil was determined by using gas chromatography-mass spectrometer. About 19, 20 and 34 compounds were identified in 7, 9, and 11-month old java turmeric. Fifteen compounds were found in all samples namely β-elemene, zingiberene, γ-elemene, β-farnesene, α-curcumene, benzofuran, α-cedrene, epicurzerenone, ar-curcumene, germacrone, aromadendrene, α–longipene, trans-caryophilene, curcuphenol, and xanthorrhizol. This study showed the level of all compound detected in 7, 9, and 11 months old of java turmeric is different.